Aung San Suu Kyi at the International Court of Justice: The Gambia's genocide case against Myanmar and its domestic ramifications - Angshuman Choudhury; Felix Heiduk (Stiftung Wissenschaft und Politik (SWP), 2019)
The recent decision by The Gambia to file a genocide case against Myanmar at the International Court of Justice (ICJ) has directed international attention again towards Rakhine State in western Myanmar, where the Rohingya people have faced discrimination and persecution for decades. What took many observers by surprise was the announcement by State Counsellor Aung San Suu Kyi that she would be travelling to The Hague to personally 'defend the national interest' and thus, by extension, the actions of her former nemesis. After all, she had enjoyed broad international support precisely for her role as leader of the National League for Democracy (NLD) and her democratic, non-violent opposition against the military dictatorship. These developments, we argue, must be understood against a wider rollback of the democratisation process. The rollback is at least partly being orchestrated by Aung San Suu Kyi and the NLD, and it could bode ill especially for the ethnic minorities in the country.
Keywords: 320